Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.17811/ebl.4.4.2015.151-160
|View full text |Cite
|
Sign up to set email alerts
|

What happens to the relationship between public debt and economic growth in European countries?

Abstract: The importance of public debt level is mainly related with its impact on economic growth. We analyze the relationship between public debt and economic growth in the core and periphery European countries. We find that higher levels of debt-to-GDP ratio have a negative impact on economic growth in all countries, with Belgium and Ireland being the most affected economies in each type of countries. Moreover, we obtain that economic growth reduces debt-to-GDP ratio and, consequently, economic growth is essential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…It is interpreted as a 1% increase in the labour force leading economic growth to increase by 0.11% in the long run. This finding is in line with [22][23][24]. Nevertheless, this finding is contradictory to the previous research finding of [25], Who reported that the labour force has a negative impact on economic growth in Ethiopia.…”
Section: Unit Rootsupporting
confidence: 62%
“…It is interpreted as a 1% increase in the labour force leading economic growth to increase by 0.11% in the long run. This finding is in line with [22][23][24]. Nevertheless, this finding is contradictory to the previous research finding of [25], Who reported that the labour force has a negative impact on economic growth in Ethiopia.…”
Section: Unit Rootsupporting
confidence: 62%
“…(2013), Furuoka (2013), Musa (2015) and Sebikabu et al. (2020).y ⇒ p , unidirectional causality, economic growth stimulates population to grow: Nakibulla (1998).p ⇔ y, bidirectional causality, population growth stimulates and is stimulated by economic growth: Garza-Rodriguez et al. (2016), Alvarez-Diaz et al.…”
Section: Population Dynamics and Economic Growth: A Review Of The Emp...mentioning
confidence: 99%
“…p ⇔ y, bidirectional causality, population growth stimulates and is stimulated by economic growth: Garza-Rodriguez et al. (2016), Alvarez-Diaz et al.…”
Section: Population Dynamics and Economic Growth: A Review Of The Emp...mentioning
confidence: 99%